Does Sales Growth Have an Effect on The Relationship Business Strategy, Multinational Companies and Tax Avoidance? - Darma, Sapta Setia; Oxadina, Apriliana (EAJ (Economic and Accounting Journal), 2023)
This research aims to empirically prove the effect of business strategy and multinationals on tax avoidance, with sales growth as a moderating variable. This research was conducted in property and real estate companies. The type of research used is quantitative with an associative method approach. The data type used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for 2017-2021. Samples were collected using a purposive sampling method. The amount of data collected is 60 observational data. The data were processed using the Eviews 9 Statistical Program to test the hypothesis using panel data regression analysis—the results of the F statistical test show that business strategy and multinationals simultaneously influence tax avoidance. The results of the t-statistical test show that business strategy has a positive effect on tax avoidance, but multi-nationality hurts tax avoidance. The MRA test results show that sales growth moderates the effect of business strategy and multinationals on tax avoidance. The novelty of this research is that in this research period, 2017-2021, by taking data for the last five years, then the result conclusions are more generalizable and better reflect the conditions that occur at the moment.